Kedudukan Hukum Harta Bersama Setelah Dinyatakan Pailit Akibat Tindakan Actio Pauliana (Studi Putusan Mahkamah Agung Republik Indonesia Nomor 211 K/Pdt.Sus-Pailit/2019) - Adiputri, Raden Ayu Farah Diva; Aritonang, Parulian Paidi (Wajah Hukum, 2025)
Actio pauliana is a legal remedy provided by law to annul the actions of a debtor that may harm creditors in the process of bankruptcy. One form of debtor actions that obstruct the fulfillment of creditors’ rights is found in the Supreme Court Decision No. 211 K/Pdt.Sus-Pailit/2019, which involves an unlawful act committed by the wife a mortgage to settle her debt. Based on this issue, the author conducts research to determine the legal position of join assets after being declared bankrupt duet o actio pauliana. The purpose of this research is to understand the legal standing of joint assets after bankruptcy is declared duet o actio pauliana and how bankruptcy law resolves joint assets issues as reflected in the decision under study. The research findings show that the actio pauliana action is the appropriate step to annul the unlawful transfer of property under the law, which is then returned to the bankruptcy estate to esnurethe fair fulfillment of creditors’ rights. The property involved in the transation must be returned to the trustee for the management and settlement of the bankruptcy estate. Additionally, the legal status of join assets resultig from actio pauliana must be borne by both the husbang and wife as long as they remain married, because during the marriage, both spouses share the responsibility for the payment obligations.